A comparative study of the value relevance of accounting information between financial and non-financial companies listed on the Ghana stock exchange. (2018) - Der, Basil Abeifaa; Masri, Masairol Haji; Abubakari, Mohammed Salisu
We investigate the value relevance of book value, earnings and dividends among financial and non-financial companies listed on the Ghana Stock Exchange from 2005 to 2014. For the sample of non-financial companies, book value and earnings are found to be value relevant. Dividends are only value relevant when earnings are split into dividends and retained earnings. For the sample of financial companies, only dividends and earnings are found to be value relevant. Book value is not value relevant. Largely, accounting information has greater value relevance for the sample of non-financial companies than the sample of financial companies. There is no difference in the explanatory power of the Ohlson (1995) model as compared to the two alternative models under investigation. Largely, IFRS adoptions have a significant effect on the value relevance of accounting information. The results have implications for both policy makers and investors.